Lighting and Air Conditioning Evaluation using Lumen and CLTD Methods: A Case Study in the Library of Politeknik ATMI Surakarta - Hoedi Prasetyo; Nicholas Lucky Baskara; Bayu Saputro; Matius Damar Adi Pradhana (Performa: Media Ilmiah Teknik Industri, 2025)
Comfort is a crucial factor in supporting the intended use of a space, including library spaces. Some previous studies have successfully examined the comfort of library spaces. However, there is still a lack of research that simultaneously examines the aspects of visual comfort, thermal comfort, and energy conservation. This study aims to evaluate the comfort of library space, including lighting, air conditioning, and energy conservation aspects, with a case study conducted in the library of Politeknik ATMI Surakarta. The research stages include data collection and calculations, followed by result analysis. Lighting calculations use the Lumen method, while cooling load calculations utilize the Cooling Load Temperature Difference method. Result analysis is carried out through a comparison between observation results and calculations, referring to several applicable standards. The research findings indicate that the lighting level in the library space needs improvement through the addition of lights and the even distribution of lighting installations. Another alternative solution is the replacement of lights with LED types that are more energy-efficient. The installed air conditioning unit in the room is in line with the cooling load requirements. However, it is recommended to replace the Window-type air conditioning unit with a Split Wall type and to exchange their locations.